Coastal Adaptation and Uncertainties: The Need of Ethics for a Shared Coastal Future - Sánchez-Arcilla, Agustín; Gracia, Vicente; Mösso, César; Cáceres, Iván; González-Marco, Daniel; Gómez, Jesús (Frontiers in Marine Science, 2021)
Coastal hydro-morphodynamics present significant uncertainties, one order of magnitude larger for sediment transport than for the driving hydrodynamics. Met-ocean factors (waves, currents, and levels essentially) are normally selected from a probability distribution, where only the central trend is considered, and then the analysis of hydro-morphodynamic processes is carried out within a deterministic framework. This analysis is often based on a non-updated topo-bathymetry, with implicit error intervals for many variables, which results in uncertainties that, unless presented from an ethical perspective, tend to hinder proactive decision making and thus result in growing coastal degradation. To address this challenge, the article starts with the uncertainty in water/sediment fluxes and resulting morphodynamic impacts under average and storm conditions, proving the need to include explicit error levels in the analysis and subsequent assessments. The article develops this approach for field and lab data, considering how they are extrapolated to estimate key variables in coastal sustainability and engineering decisions, illustrated in terms of the longshore sand transport. Such a key variable estimation presents large uncertainties and thus requires a stricter ethical approach for extreme events, which serves to illustrate the transmission of uncertainties. The article concludes with a short overview of the implications that these uncertainties may have for coastal risk assessments and proactive decision making, discussing how large error levels without a suitable ethical assessment may result in socio-economic mistrust, which will limit the necessary optimism to address future coastal sustainability.